Inverse Split Majority Dominating Set of a Graph - Manora, J. Joseline; Vignesh, S.; Jayasimman, I. Paulraj (Communications in Mathematics and Applications, 2021)
In this paper, we introduced an inverse split majority dominating set of a graph \(G\). Inverse split majority domination number \({γ }^{-1}_{SM}(G)\) is determined for some classes of graphs. Some important results and characterization theorems on \({γ }^{-1}_{SM}(G)\) are established. Many Bounds on inverse split majority domination number and its relationship with other domination parameters are also obtained.
Keywords: Majority domination number; Inverse majority domination number; Split dominating (SD) set; Inverse Split Majority dominating (ISMD) set; Inverse Split majority domination number.